বাংলাদেশের শিক্ষাব্যবস্থা = Management of education in Bangladesh - শাহেদ, হোসনে আরা (ঢাকা : সূচীপত্র, 2002)
Contributed articles on existing system of education in Bangladesh and proposals for its improvement.
Includes bibliographical references.
BIED
Complimentary copy from BIED
In Bengali.
Keywords: Education -- Aims and objectives -- Bangladesh